WOMEN ISSUES IN TWO SHORT STORIES BY RATNA INDRASWARI IBRAHIM: A STUDY OF COMPARATIVE LITERATURE TOWARD TWO SHORT STORY; ‘RAMBUTNYA JUMINTEN’ AND ‘BAJU’ - Putri Bestari Mardani; Devi Suprasti; Juni Aratika (Universitas Muhammadiyah Surakarta, 2017)
The issue of women’s life has always been an interesting topic to be discussed. This kind of issue has been widely delivered by story writers, which is by placing women as the main character in his/her work. It aims to convey the results of their thoughts in the form of literary works. As already been known, literary works are one of an essential container to describe the reflexivity of society. Sensitive issues could be freely expressed in literary works. As an example is the issue of women which is described in short stories form and published through the mass media. The aims of this paper are to explain the forms of problems or issues revolving women that are presented in the ‘Baju’and ‘Rambutnya Juminten’text by Ratna Indraswari Ibrahim. This study uses the theory of feminism by Simone de Beauvoir. Beauvoir suggests that women are considered as the second-class citizens or as the second sex due to patriarchal power, a notion that can lead to gender inequality (Kuntowijoyo 1987: 136). Based on the study, it was found that both texts reveal various forms of women’s issues, which are patriarchy and gender constructions. Both traditional women and an empress with a high social position experience the same issue. Although the two female figures were trying to speak up, they are being ignored. This is because there is a widely known stereotype that states that women are emotional and irrational, so women are considered unable to manage their own lives and are not suitable to speak in a public sphere. Keyword: comparative literature, feminism, short story, Ratna Indraswari, women issues.